The Influence of Globalization and Modernization on the Implementation of Immigration Inspection SOPs by the Class I Special Immigration Office TPI Ngurah Rai as an Effort to Prevent Immigration Violations by Foreign Nationals (WNA) - Jimmi Pesta Sirait; Cokorde Istri Dian Laksmi Dewi; Benyamin Tungga (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study examines the implementation of the Standard Operating Procedure (SOP) for immigration inspection by the Class I Special Immigration Office at TPI Ngurah Rai as a preventive measure against immigration violations committed by foreign nationals. The background of this research stems from the increasing influx of foreigners into Indonesia, particularly through I Gusti Ngurah Rai International Airport in Bali, which has been accompanied by a rise in administrative violations such as overstaying and visa misuse. The study employs a juridical-empirical approach by analyzing the relevant legal frameworks and their practical application in the field. The findings indicate that the implementation of the SOP, including the use of autogate technology and the immigration information system, has improved the efficiency and accuracy of inspection procedures. However, the autogate system also creates potential gaps in oversight that may be exploited by foreign nationals seeking to bypass regulations. Therefore, strengthening the SOP is necessary through regular evaluation, capacity building of personnel, and balanced integration of manual and digital systems. This study recommends a review of the autogate SOP to ensure its alignment with the principles of legal certainty, national security, and orderly immigration administration. Keywords: Standard Operating Procedure (SOP), Immigration Violations, Autogate